Unraveling the environmental pollution in agroecosystems: multicompartmental occurrence and toxicity assessment of pesticides and trace metals in the Sogamoso River Basin, Colombia (2024)
Pesticides and metals are perhaps the most studied contaminants worldwide, linked as environmental stressors due to their increased occurrence and accumulation in soils, sediments, and water. They occur in complex mixtures in agroecosystems posing potential risk for biodiversity and human health. Agricultural lands in Colombia faces several environmental challenges. Most of them, especially horticulture systems, are managed by smallholders and few is known about their patterns of conventional use of agrochemicals and the impacts on natural resources. The crop of onion (Allium cepa L.) is representative of this problem. It presents a growing trend in national vegetable production, it is mainly handled by smallholders, and is characterized by a high dependence on agrochemicals. Hence, it is necessary to determine their toxicity in field conditions and to develop monitoring approaches to assess the environmental status of the intensive agriculture areas and its impact on the surrounding ecosystems at basin scale. The main objective of the thesis was to assess the pesticide and trace metals pollution in a tropical agroecosystem, its multicompartmental occurrence, and cytogenetic toxicity biomarkers in Allium cepa L. crops. To assess the multicompartmental occurrence of pollutants, pesticides were quantified in soils, sediments and water, and trace metals in soils and sediments. Then, the toxicological impact of the resulting mixtures was assessed in soils using the Allium cepa L. tests, with an on-site approach. Also, different indices of pollution and ecological risk were assessed for soil, sediment, and water systems. This objective was pursued through two studies conducted in the department of Boyacá, Colombia, in the surrounding of the irrigation district of the Chicamocha River, belonging to the basin of the Sogamoso River and tributaries of the Magdalena River. The first project addressed the occurrence of pesticides in soils, sediments, and water around the influence area of conventional crops of onion in the basin of the Sogamoso river. Legacy organochlorines (22), organophosphates (7), and azole fungicides (5) were analyzed using GC-MS. Trace metals Cd, Cr, Cu, Hg, Ni, Pb, and Zn were quantified by AAS. Toxic units (TU) and hazard quotients (HQ) were calculated to assess the mixture toxicity. Pesticide levels varied widely, with soil samples showing concentrations between 214.2 and 8497.7 µg/kg, sediment samples ranging from 569.6 to 12768.2 µg/kg, and water samples containing 0.2 to 4.1 µg/L. Furthermore, by employing the partition coefficient (Kd) and the fraction of organic carbon (foc), it was possible to analyze the distribution of most pesticides in sediments, suspended particulate matter (SPM), and water, although this method was not applicable for soil samples. Trace metals were measured in soils (n=19) in average concentrations of 1.1±1.6 for Cd, 18.9±5.1 for Cr, 24.4±16.8 for Cu, 0.060±0.017 for Hg, 10.3±4.1 for Ni, 11.9±20.2 for Pb, and 350.4±523.9 for Zn. In sediments (n=10), the average concentrations were 0.5±0.1 for Cd, 17.6±7.2 for Cr, 79.9±75.9 for Cu, 0.034±0.024 for Hg, 13.4±9.8 for Ni, 18.4±25.3 for Pb, and 133.1±44.2 for Zn. TU >1 and HQ >1 were observed respectively in 10% and 42% of soil samples, 100% of sediments, and 30% and 50% of water samples. These indices suggest most of the sampling sites had pollution levels of environmental concern. The second project investigated toxicity biomarkers in agricultural soils, examining the relationship between cytogenetic biomarkers in Allium cepa L. and the complex mix of pesticides and trace elements in soils of conventional, conversion, and organic crops The analysis involved GC-MS/MS and LC-MS/MS for pesticide detection, ICP-MS for arsenic, cadmium, lead, and zinc, ICP-OES for chromium, copper, nickel, and selenium, and a direct analyzer for mercury. Microscopic examination of root meristematic cells of Allium cepa L. was used to assess cytogenetic impacts. In soils from conventional farms, 26 pesticides were identified, whereas in organic farms, pesticide levels were below detection limits. Average concentrations of As, Cd, Cr, Ni, Pb, and Se were higher in conventional farm soils than in organic ones. Moreover, conventional soil samples showed increased cytotoxicity and genotoxicity biomarkers, which correlated with the levels of pesticides and trace elements, pollution indices, and hazard quotients. A discriminant function incorporating the mitotic index, chromosomal aberrations, and nuclear abnormalities effectively differentiated the samples based on the type of farming. The two projects together indicated the fate of legacy organochlorine pesticides across the basin and the potential transport and distribution of complex mixtures of pesticides and trace metals from croplands to the river. This research demonstrated the sensitivity of Allium cepa L. to the toxicity of complex mixtures in field crops and its potential as an in-situ approach for soil health monitoring in organic and conventional crop systems. Conventional agriculture is a source of diffuse pollution; the detection of pollutants along the river indicated the need to prevent ecological and human health risks due to their capacity to remain active in the environment. This was comprehensive view of the impacts of agriculture, contributing to the identification of actions oriented to the sustainable management of agroecosystems.